Pengaruh Brand Ambassador Terhadap Minat Beli Produk Maybelline New York Melalui Sikap pada Iklan Sebagai Variabel Mediasi - Marischa Aqilah Faradilla; Sonja Andarini (Universitas Sam Ratulangi, 2022)
Maybelline New York is one of the most famous cosmetic products, one of which is in Indonesia. Maybelline New York has issued more than 200 cosmetic products by utilizing the latest technological sophistication in the latest trends. Just like any other cosmetic business, Maybelline New York certainly wants its product sales to always increase, but in fact there has been a decline in sales in recent years. This study aims to determine the effect of the brand ambassador